Caring for Oneself or for Others? How Consistent and Inconsistent Profiles of Health-Oriented Leadership Are Related to Follower Strain and Health - Klug, Katharina; Felfe, Jörg; Krick, Annika (Frontiers in Psychology, 2019)
Health-oriented leadership consists of three dimensions that contribute to employee health: staff care, i.e., health-specific follower-directed leadership, as well as both leaders’ and followers’ self care, i.e., health-specific self-leadership. This study explores profiles of follower self care, leader self care and staff care, and investigates the relationships with follower health in two samples. We identified four patterns of health-oriented leadership: A consistently positive profile (high care), a consistently negative profile (low care), and two profiles showing inconsistencies between follower self care, leader self care and staff care (leader sacrifice and follower sacrifice). The high care profile reported the best health compared to both the low care profile and the inconsistent profiles. The follower sacrifice profile reported more strain than the leader sacrifice profile, while strain and health levels were the least favorable in the low care profile. Findings reveal that (in-)consistency between follower-directed leadership and self-leadership contributes to follower strain and health.